Colostomy and Ilestomy: Therapeutic Strategy? - Hernández, José Luis García; Cabello, José de Jesús Urbina; Suárez, Ivonne Alondra León; Avila, Juan Antonio Juarez; Frausto, Lya Yadira Celada; Ríos, Aldebharán Avila; Sanciprián, Rafael Martínez; Adolfo, García Sánchez Morelos (British Journal of Healthcare and Medical Research, 2025)
Introduction: Colostomy and/or ileostomy is an opening in the abdomen by means of a surgical intervention, with the function of evacuating fecal matter or gastrointestinal waste. Objective: To describe the experience in public hospitals when performing colostomy and ileostomy surgeries on patients. Method: A multicenter study with a retrospective, longitudinal, observational and descriptive design of the Surgery and Coloproctology Service, a study of five second and third level health care hospitals in Mexico City and the State of Mexico. Results: Of 1,693 cases, a total of 91 patients with intestinal stomas exclusively were documented, with complete records/files of a distribution by sex of 47 men representing 51.64% and 44 women representing 48.35%. With an average age of 44 years and range from 21 to 95 years. The most frequent etiologic diagnosis for creating a stoma is complicated acute appendicitis. In specific pathologies, where other surgeons perform a stoma, the authors of this study perform the medical colostomy strategy. Discussion: When is an ileostomy performed? This decision must be considered in true medical situations. Preventive ileostomy has unique excretion characteristics: aqueous, highly alkaline deposition with proteolytic enzymes. The initial daily stool volume in the new ostomy is approximately 1200 ml, and after a period of bowel adaptation, it remains between 500- and 800-ml. Short-term complications may include stoma retraction, necrosis, high-output stoma, and obstruction of the stoma orifice; long-term complications include stoma prolapse, strictures, skin irritation, and peristomal hernia. Conclusions: Ileostomy and/or colostomy are therapeutic arsenals that, if well indicated or justified, are a timeless benefit or asynchronism when created, impacting the life of the patient in an emergency or programmed by the underlying disease. The controversy of the current surgical conduct of performing a stoma of the small intestine or colon is condemnatory by the surgical community, however, it is still a saving, timely or excellent strategy, depending on the context of each patient.